P.E. 4 : team sports - Tulio, Doris D.; Bueta, Ma. Liza A.; Sarmiento, Estelita F.; Battung, Josephine B. (Makati : Katha Publishing Co., Inc., 2004)
Presents the fundamental concepts of Basketball and Volleyball to help the students improve their skills. Quickly it became apparent that there was no suitable skill book that combined the presentation of basic concepts and the developmetn of skills in basketball and volleyball.
Part I Volleyball -- Part II Basketball.
Keywords: BASKETBALL -- TEXTBOOKS; VOLLEYBALL -- TEXTBOOKS